Communicating through e-mail : possible problems faced among employees and possible solution taken in the environmental protection department Kota Kinabalu / Yunisia Yunos - Yunos, Yunisia (2009)
Globalizations bring people to the new world. Technology is become more sophisticated and challenge people minded. Technology helps people in doing their job, making money, connecting people wherever they are and do many tiling's, in the work place especially it very helpful. In order for people go for it there are too many obstacle come across that make people refuse to go through with e-mail due to the some prevention. E-mail is one from many approaches in technology that are connecting peoples wherever they are; it can help people communicate through it. Therefore, in many working place e-mail was use as the communication tools. However as having research of it, result that there are still have to many obstacle that people especially employees faced in order to used it. The lack of tools becomes one of the possible problems of communication through e-mail. Perhaps that it will be solving by using alternative to aid more facilities in the offices.